PELATIHAN DESAIN GRAFIS CANVA UNTUK MENINGKATKAN KREATIVITAS SISWA - Anwar, Rohimatul; Anwar, Rosyida Nurul (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
This one-group pretest–posttest, service-learning Canva training for Grade VII students at SMPN 2 Wungu aimed to enhance students’ visual creativity and digital literacy. The program followed needs analysis, preparation, delivery, and evaluation within a single intensive session. The primary instruments comprised a poster assessment rubric (four indicators: layout, typography, color, and message clarity; 1–4 scale; two independent raters) and a 10-item perception questionnaire (1–4 scale; internal reliability estimated). The study involved 20 students selected proportionally from several classes. Results show an increase in mean product scores from 1.8 (pre) to 3.0 (post), i.e., Δ≈+1.2 points, with the proportion rated “good–very good” on color and layout reaching ≥75%. Additionally, 85% of respondents rated the training “useful/very useful” for visual and presentation tasks. These findings indicate that a short, structured, template-based workshop can reduce the technical burden of operating the app while directing attention to design problem-solving. Ethical procedures were observed through school approval, data anonymization, and consented documentation. Limitations include the single-session duration and small sample size, therefore 2–3 follow-up sessions with metric monitoring (consistent rubrics, scaffolded tasks) are recommended to provide stronger evidence of creativity gains.